Sleep Status and Its Association On Occupational Performance Among Nurses - Saloma, Pawi; Laurita, Estiny; Ong, Mei Fong (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
Sleep is an activity that allows our body to have enough rest after many hours of working throughout the whole day. Only through sleep do our brain and muscles are able to relax. Sleep expert says the amount of sleep each person need is largely dependent on the individual. Compared to non-shift workers or day workers, shift workers are more prone to experience sleep disorders simply due to the non-standard working time. Many studies have reported that these sleep disorders tend to affect the occupational performance of an individual. Among possible consequences include increase mortality, morbidity, accidents and errors, absenteeism in workplace, decrease in productivity, and deterioration of personal and professional relationship problems caused by working in shifts are not uniform among shift workers, and some suffer while others thrive. Shift workers on a night shift (hereafter night shift workers) slept less than the shift workers on a day shift (hereafter day shift workers) or day workers did, whereas the working hour for night shift workers were longer (Son, Kong, Koh, Kim & Harma, 2008). Data inclusive of demographic variables, measurement of sleep status and occupational impact was collected from 213 nurses working in 10 selected wards in Sarawak General Hospital in 2017. Findings revealed that out of 213 nurses, 53.1% reported of being moderately sleepy while 12.2% are very sleepy while working. Reporting on the association of sleep status with occupational performance, 55.4% reported of slight impact, 41.3% reported of moderate impact and another 3.3% reported of high impact. In this study, the relationship between demographic variables and the prevalence of sleep status was also investigated. Working area (ward/unit) is significantly associated with the prevalence of sleep status (p-value of 0.000). In conclusion, more than half of the respondents in this study reported of being sleepy while working thus pose great danger to patients under their care as this can affect their occupational performance. Further research need to be done to include on emotional status and physical fitness of respondents as this may affect their ability to cope with shift work and thus determining sleep disorder.